Genotyping the local banana landrace groups of East Africa - Karamura, D.; Kitavi, M.; Nyine, M.; Ochola, D.; Ocimati, W.; Muhangi, S.; Talengera, D.; Karamura, E.B. (International Society for Horticultural Science, 2016)
Crop landraces (largely resulting from adaptation and continuous selection by farmers) are more diverse within field populations than modern cultivars (produced by deliberate crossing), yet their distribution has continued to shrink in the past decades. The temporal dynamics of this shrinking is little known. The analysis of genetic variation within and between landraces is essential for making efficient breeding and conservation decisions with the available variability. Seven diploid landraces originally from Tanzania, 37 triploid landraces (24 East African highland bananas (EAHB); 5 'Ilalyi' (AAA genome), and 8 ill-defined types from Tanzania), 6 exotic triploids, and 3 exotic diploids originally from the International Transit Center were genotyped with simple sequence repeat (SSR) markers. This study sought to understand the genetic relationship between the EAHB and the diploid landraces and other banana groups (local triploid landraces, and introduced (exotic) cultivars) so as to decide whether to include the diploids in the breeding scheme of EAHB. Results showed the highest average genetic distance (degree of genomic difference by proportion) within the diploids (0.5666), followed by the hybrid triploids (0.4568) and the lowest within the 'Ilalyi' (0.0748) and the EAHB (0.0827) landraces. The variation within each clone set of EAHB was higher in 'Nakitembe' (0.0948) and 'Musakala' (0.1052). These two are commercial clone sets whose variation may be due to high and long-term selection pressure. In contrast, between the banana groups, the diploid landraces were more distant (highest average genetic distance) from the triploid landraces (0.4351-0.4430) and could thus provide useful breeding traits. On the other side, the triploid landraces had a narrow genetic base which should be broadened. Results did not identify those local east African diploids closest to the EAHB or other local triploids, although local diploids show breeding potential. This could widen the genetic base and probably improve performance of the triploid landraces.